Antagonistic Activities and Probiotic Potential of Lactic Acid Bacteria Derived From a Plant-Based Fermented Food - Choi, Ah-Rang; Patra, Jayanta Kumar; Kim, Wang June; Kang, Seok-Seong (Frontiers in Microbiology, 2018)
In this study, antagonistic activities and probiotic potential of lactic acid bacteria (LAB) derived from a plant-based fermented food, kimchi, were demonstrated. The cell free supernatants (CFS) from Lactobacillus curvatus KCCM 43119, Leuconostoc mesenteroides KCCM 43060, Weissella cibaria KCTC 3746 and W. koreensis KCCM 41517 completely inhibited the growth of foodborne pathogenic bacteria, while neutralized CFS (pH 6.5) partially inhibited the growth. The competition, exclusion, and displacement of foodborne pathogenic bacteria by the LAB strains from adhesion to HT-29 cells were investigated. The LAB strains were able to compete with, exclude, and displace the foodborne pathogenic bacteria. However, the degree of inhibition due to the adhesion was found to be a LAB strain-dependent phenomenon. The LAB strains showed high coaggregation with foodborne pathogenic bacteria, and they also exhibited high resistance to acidic condition. Except W. cibaria KCTC 3746, all LAB strains were capable of surviving in the presence of bile salts. Furthermore, while all LAB strains were resistant to chloramphenicol, kanamycin, streptomycin, gentamycin, and erythromycin, only W. cibaria KCTC 3746 and W. koreensis KCCM 41517 displayed resistance to vancomycin. These results suggest that the LAB strains derived from kimchi exerted antagonistic activities against foodborne pathogenic bacteria with probiotic potential.